Coronavirus Disease 2019 Infection in Children With Sickle Cell Disease: Case Series From Oman. Issue 7 (October 2021) - Al Sabahi, Amal; Al Maskari, Nawal; Al Busaidi, Ibrahim; Albiroty, Khalil A.; Alkhamisy, Ahmed; Al Hinai, Karima; Al Hinai, Mohammed; Al Mashaikhi, Nawal; Alkendi, Jalila
Abstract : Background: In March 2020, WHO announced Coronavirus Disease 2019 (COVID-19) outbreak a global pandemic. During this pandemic, patients with sickle cell disease (SCD) have been placed in the "high-risk" category of the population. Although there are numerous publications describing COVID-19 in adult patients, pediatric data are still limited. Observation: Herein, we report case series of 5 sickle cell disease Omani children who got infected with COVID-19; illustrating their different ways of presentation, management and highlighting the outcomes. Conclusion: Although SCD patients are considered as a high-risk group, all of the observed patients, and whose cases are reported here, have recovered. A large scale of SCD cases should be studied to reach more conclusive results.